Gut dysbiosis as a potential driver of Parkinson’s and Alzheimer’s disease pathogenesis - Pfaffinger, Jacob M.; Hays, Kallie E.; Seeley, Jason; Ramesh Babu, Priyadharshine; Ryznar, Rebecca (Frontiers in Neuroscience, 2025)
The prevalence of neurodegenerative diseases such as Parkinson’s disease (PD) and Alzheimer’s disease (AD) in the U.S. is expected to increase as the population ages. Despite significant advancements in neurodegenerative research, the initiating events remain unclear, and no treatments currently exist to stop or reverse disease pathogenesis. Emerging studies highlight the importance of the gut microbiome and gut-brain-axis in the pathogenesis of many human diseases. This narrative review aims to integrate current research investigating how gut microbial dysbiosis may influence the development and progression of AD and PD. First, we provide an overview of the pathological features and disease mechanisms characteristic of AD and PD. Next, we summarize existing research on the microbiome–gut–brain axis and how alterations in gut microbiota composition may influence these neurological diseases. We then focus on specific bacterial taxa identified in fecal samples from AD and PD patients, highlighting differences from healthy controls and emphasizing taxa known to produce immunologically relevant metabolites and antigens. Specifically, we examine reductions in short-chain fatty acid (SCFA)-producing bacteria and increases in lipopolysaccharide (LPS)-expressing bacteria that may drive neuroinflammation and contribute to protein misfolding. Finally, this review presents hypothesized mechanisms by which microbial products such as SCFAs and LPS may interact with host physiology to modulate disease pathogenesis. These include pathways involving systemic inflammation, blood–brain barrier permeability, and neural propagation via the vagus nerve or olfactory bulb. Further research is necessary to determine the causes and effects of bacterial level shifts, but understanding the mechanistic roles of these bacterial products in AD or PD pathogenesis could allow for personalized targeted therapies to either slow or potentially reverse the disease process.